The Test of Sports and Folk Narratives with the Notion of Haram: Citing the Example of the Branch of Wrestling - Yeşildal, Ünsal Yılmaz (Religions, 2024)
Culture consists of material and spiritual values and tools that a nation has accumulated in the historical process. In addition to the most basic contexts such as language and religion, contexts such as sporting activities, art, public medicine, and the public calendar are also important environments that reveal their own cultural elements. Among these contexts, religion is very effective in shaping the daily life of the individual and, thus, society through the rules it enjoins. Religion does not dominate only the world of belief of the individual. Through the world of belief, it also directs their relations with the social institutions they are involved in. Sport is one of the most important activities and social institutions that stand out with various functions in daily life, with wrestling being one of the branches of sports that have emerged as a result of the imitation of the struggle of human beings with nature and other creatures with which they share nature. In particular, those involved in the nomadic way of life had to hunt in order not to starve and fight in order to survive. Wrestling, which emerged as a result of these obligations, held an important place among all Turks in the world for a period of time, especially in the transition periods of life, such as birth, marriage, and death. One of the conditions set forth by women as a condition of marriage was that their suitor defeated them in wrestling. Examples of this condition are also observed in literary texts belonging to different periods when Turks were not yet acquainted with Islam and the concepts of halal and haram, which entered their lives together with Islam. According to the provisions of the Holy Qur’an, right/unprohibited thoughts and actions are associated with the words good and halal, while wrong/prohibited thoughts and actions are associated with the words sin and haram. In this study, the social and cultural phases of wrestling as a sports branch among Turks in the historical process will be evaluated on the basis of the history of religions and religious references, in addition to the literary texts belonging to historical periods when Turks were members of different religions, in the context of two events that have been experienced and reported in the news. The study was carried out using the method of document analysis, a method of qualitative research, and the data obtained by this method were evaluated using content analysis. The narratives of Alıp Manaş, Alpamış, Alpamıs, Alıpmenşen, and Bamsı Beyrek, which are evaluated in this context, belong to the periods when the Turks had not been introduced to Islam or had only recently been introduced to it. Alıp Manaş was collated from different Turkic tribes such as the Altais, Alpamış from the Uzbeks, Alpamıs the Kazakhs/Karakalpaks, Alıpmenşen the Bashkirs/Tatars, and Bamsı Beyrek the Oghuz Turks. The narratives of Kirmanshah, Köse Kenan-Dânâ Hanım, Bey Böyrek, Shah Ismail, and Yaralı Mahmut, which are evaluated in the study, belong to the periods when the Turks became Muslim en masse, and are related only among the Oghuz Turks. These narratives are included in the study because they are similar to Alıp Manaş, Alpamış, Alpamıs, Alıpmenşen, and Bamsı Beyrek and they belong to the period when Islam was largely established among the Turkish masses in Anatolia. The effect of the new religion on wrestling, which is a branch of sport, will be revealed through these narratives belonging to different tribes and religious periods. Once more, an event that occurred in recent history, and was the subject of the news, was subjected to document analysis, and content analysis was carried out through the text of the news and evaluated in the context of the study. This study aims to explain the effect of religious rules on sports branches with theological, folkloric, and sociological references based on ancient literary texts belonging to the Turks and two incidents which were experienced.